Infections caused by Mycobacterium abscessus: epidemiology, diagnostic tools and treatment. Issue 12 (1st December 2016) - Mougari, Faiza; Guglielmetti, Lorenzo; Raskine, Laurent; Sermet-Gaudelus, Isabelle; Veziris, Nicolas; Cambau, Emmanuelle
ABSTRACT: Introduction: Mycobacterium abscessus is an emerging mycobacteria that is responsible for lung diseases and healthcare-associated extrapulmonary infections. Recent findings support its taxonomic status as a single species comprising 3 subspecies designated abscessus, bolletii and massiliense . We performed a review of English-language publications investigating all three of these subspecies. Areas covered: Worldwide, human infections are often attributable to environmental contamination, although the isolation of M. abscessus in this reservoir is very rare. Basic research has demonstrated an association between virulence and cell wall components and cording, and genome analysis has identified gene transfer from other bacteria. The bacteriological diagnosis of M. abscessus is based on innovative tools combining molecular biology and mass spectrometry. Genotypic and phenotypic susceptibility testing are required to predict the success of macrolide (clarithromycin or azithromycin)-based therapeutic regimens. Genotyping methods are helpful to assess relapse and cross-transmission and to search for a common source. Treatment is not standardised, and outcomes are often unsatisfactory. Expert commentary: M. abscessus is still an open field in terms of clinical and bacteriological research. Further knowledge of its ecology and transmission routes, as well as host-pathogen interactions, is required. Because the number of human cases is increasing, it is also necessary to identify more active treatments and perform clinical trials to assess standard effective regimens.